The effects of intertrial interval and instructional format on skill acquisition and maintenance for children with autism spectrum disorders. Issue 4 (26th May 2016) - Cariveau, Tom; Kodak, Tiffany; Campbell, Vincent
Abstract : We replicated and extended the study by Koegel, Dunlap, and Dyer (1980) by examining the effects of 3 intertrial‐interval (ITI) durations on skill acquisition in 2 children with autism spectrum disorders. Specifically, we compared the effect of short (2 s), progressive (2 s to 20 s), and long (20 s) ITIs on participants' mastery of tacts or intraverbals presented in massed‐trial and varied‐trial instructional formats. We also measured (a) stereotypic and problem behavior during the ITI, (b) maintenance of skills, and (c) responding to novel adults and settings. Results showed that short ITIs in a varied‐trial format produced the most efficient acquisition of skills; however, most ITI durations produced more efficient skill acquisition in a varied format compared to a massed format. The trial format and ITI duration associated with the lowest levels of stereotypic and problem behavior during the ITI and responding during maintenance and novel adult and setting probes differed across participants.